The correlation between dysfunctional intestinal flora and pathology feature of patients with pulmonary tuberculosis - Ye, Shiqing; Wang, Liang; Li, Shengkai; Ding, Qingyong; Wang, Yu; Wan, Xinxin; Ji, Xiaoyun; Lou, Yongliang; Li, Xiang (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Recent studies have provided insights into the important contribution of gut microbiota in the development of Pulmonary Tuberculosis (PTB). As a chronic consumptive infectious disease, PTB involves many pathological characteristics. At present, research on intestinal flora and clinical pathological Index of PTB is still rare. Methods We performed a cross-sectional study in 63 healthy controls (HCs) and 69 patients with untreated active PTB to assess the differences in their microbiota in feces via 16S rRNA gene sequencing. Results Significant alteration of microbial taxonomic and functional capacity was observed in PTB as compared to the HCs. The results showed that the alpha diversity indexes of the PTB patients were lower than the HCs (P<0.05). Beta diversity showed differences between the two groups (P<0.05). At the genus level, the relative abundance of Bacteroides, Parabacteroides and Veillonella increased, while Faecalibacterium, Bifidobacterium, Agathobacter and CAG-352 decreased significantly in the PTB group, when compared with the HCs. The six combined genera, including Lactobacillus, Faecalibacterium, Roseburia, Dorea, Monnoglobus and [Eubacterium]_ventriosum_group might be a set of diagnostic biomarkers for PTB (AUC=0.90). Besides, the predicted bacterial functional pathway had a significant difference between the two groups (P<0.05), which was mainly related to the nutrient metabolism pathway. Significant alterations in the biochemical index were associated with changes in the relative abundance of specific bacteria, the short chain fatty acid (SCFA)-producing bacteria enriched in HCs had a positively correlated with most of the biochemical indexes. Discussion Our study indicated that the gut microbiota in PTB patients was significantly different from HCs as characterized by the composition and metabolic pathway, which related to the change of biochemical indexes in the PTB group. It was hypothesized that the abovementioned changes in the gut microbiota could exert an impact on the clinical characteristics of PTB through the regulation of the nutrient utilization pathway of the host by way of the gut-lung axis.